THE EFFECT OF SUITABILITY BETWEEN PERSONALITY TYPES AND WORK ENVIRONMENT MODELS ON JOB SATISFACTION - Ariani, Alpha; Karyati, Faridah (IJBLE Scientific Publications Community Inc., 2023)
Job satisfaction is essential in improving employee performance and productivity so that the institution can realize its goals. One factor that influences job satisfaction is employees' personality characteristics. This study aims to determine the effect of suitability between personality types and work environment on job satisfaction. The research was conducted at the Faculty of Teacher Training and Education, XYZ University, with a sample of 24 lecturers. Data was collected through the questionnaires and analyzed with simple linear regression analysis. The results showed no significant effect of the suitability between personality type and work environment on job satisfaction; the contribution is only 5.3%.